A Study of relationship between mental health and smoking among adolescences in Tanjong Malim District - Che Zulkifli, Nurul Izzati; Mohammed, Nor Firdous (Jurnal Pendidikan Bitara UPSI, 2020)
The objective of this study was to determine the relationship between mental health and smoking among adolescents. The method used for this research was cross sectional design.  The sample involved 120 secondary school students which aged 13 to 15 years old and were selected using convenience sampling. The instrument used were Problem Oriented Screening Instruments for Teenagers (POSIT) and Global Youth Tobacco Survey (GYTS). Pearson’s Correlation analysis used to measure the objective. The result illustrated that there were significant relationship between mental health and smoking among adolescents. As conclusion, mental health was correlated with smoking. Thus, the future study needed to be conducted to identify the factors associated to it.